1993
DOI: 10.1116/1.578723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface-activated reaction kinetics on low-pressure chemical vapor deposition conformality over micro features

Abstract: The coupled effect of molecular scattering and surface-activated reactions on low-pressure chemical vapor deposition (LPCVD) film conformality is investigated. Using a single-precursor two-step surface-activated deposition as an example, film conformality can be found to depend on two first-principle dimensionless parameters-Sc, the intrinsic sticking coefficient, and Sa, the surface saturation factor. An analytical integral material balance formulation, developed for the feature-scale molecular transport, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This process can induce a local averaging of the solid angles, improving the conformity. Nevertheless, several studies [31]- [35] previously demonstrated that the influence of the surface diffusion on the conformity is very low in most cases.…”
Section: Elements Of Conformity Theorymentioning
confidence: 98%
“…This process can induce a local averaging of the solid angles, improving the conformity. Nevertheless, several studies [31]- [35] previously demonstrated that the influence of the surface diffusion on the conformity is very low in most cases.…”
Section: Elements Of Conformity Theorymentioning
confidence: 98%
“…We will let , , and (molecule/ m s) denote the adsorption, desorption, and surface reaction rate constant, respectively. Similar to [21], let the adsorption probability of the precursor be (unitless) on available sites (zero on occupied sites), the surface coverage of available sites be (unitless), the surface coverage of occupied sites be (unitless), and (molecule/ m s) be the precursor impingement flux. Then the adsorption rate (molecule/ m s) will be equal to the depletion rate of in dynamic balance.…”
Section: A Mathematical Formulationmentioning
confidence: 99%
“…where (unitless) accounts for all first-order geometrical effects. The limiting cases of (adsorptionlimited) for a first-order reaction and (surfacereaction-limited) for a zero-order reaction is well illustrated in [21]. Moreover, if ( m) is defined as a phenomenological length to express the thickness of a region above the surface profile, and if the reaction site density is assumed to be constant within this region, the deposition rate modulation factor can be expressed as…”
Section: A Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, existing computer models cannot accurately predict deposition profile and sealing conditions of surface microcavities. Although computational models and tools have been developed and proven successful for predicting step coverage on relatively simple geometries (e.g., isolation trenches or vias in integrated circuit processes) [19]- [21], complex three-dimensional structures encountered in MEMS pose new challenges. The simulation program, SPEEDIE, has not been able to successfully predict the deposition thickness required for sealing.…”
Section: Introductionmentioning
confidence: 99%